The Main Components Of The Tahfiz Teaching Model With ICT Elements: An Evaluation With The NGT Application - Mardhiah Yahaya; Azmil Hashim; Raj Ali Zahid Elley; Rohana Zakaria; Siti Rosilawati Ramlan; Muhammad Fairuz A.Adi; Miftachul Huda (Hunan University, 2024)
Volume: 49 No: 1 (pages: 8-13)